2009
DOI: 10.1002/lary.20499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on quality of life following sinus surgery: 4‐year follow‐up

Abstract: Objectives The purpose of this study is to report on long-term outcomes in a prospective study comparing the quality of life outcomes in smokers and non-smokers undergoing functional endoscopic sinus surgery. Study Design Prospective clinical trial. Methods A total of 235 patients were prospectively enrolled at a single tertiary academic center. Preoperative SNOT-20 scores and comprehensive demographic and smoking data were obtained. Preoperative SNOT-20 scores were compared to postoperative SNOT-20 scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 12 publications
2
32
2
2
Order By: Relevance
“…Patients were considered smokers if they reported regular or ongoing smoking in the 12 months prior to surgery. [25,26] Patients who reported never having smoked cigarettes on a regular basis were considered as nonsmokers.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were considered smokers if they reported regular or ongoing smoking in the 12 months prior to surgery. [25,26] Patients who reported never having smoked cigarettes on a regular basis were considered as nonsmokers.…”
Section: Methodsmentioning
confidence: 99%
“…While these current studies demonstrate that passive and active smoking contribute to CRS, long-term results on smoking after FESS have not been sufficiently evaluated [20]. Our previously published data show that smokers actually have similar if not improved quality of life scores compared to nonsmokers and that smoke-induced CRS may represent a different subset of disease [18,19,20]. The present study showed a trend towards an increased prevalence of nasal polyposis and revision surgery in the nonsmoking group, although these findings did not reach statistical significance (p = 0.107 and 0.45, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Our data previously published in ‘The effects of smoking on short-term quality of life outcomes in sinus surgery' [18] demonstrated that smokers actually achieved greater short-term benefits compared to nonsmokers. This was further investigated in our study ‘Effects of smoking on quality of life following sinus surgery: 4-year follow-up' [19], which also showed that both smokers and nonsmokers continued to maintain similar improvements in SNOT-20 scores. In this article, we aim to review the same group of patients 10 years after sinus surgery to further elucidate the long-term effects of smoking and sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, DAS et al [56] examined the QoL in a prospective study of 235 (21.3% smokers) undergoing surgery (FESS). SNOT-20 scores were obtained before and after surgery.…”
Section: Copd Smoking and Sinonasal Quality Of Lifementioning
confidence: 99%